HEPATITIS-B VACCINATION STATUS AND KNOWLEDGE, ATTITUDE AND PRACTICE OF HIGH RISK HEALTH CARE WORKER BODY SUBSTANCE ISOLATION - Quddus, Mashaal; Jehan, Mussarrat; Ali, Nafisa Hassan (Journal of Ayub Medical College Abbottabad, 2015)
Background: HBV infection is occupational risk for health care worker (HCW). They play an important role in dissemination of hepatitis B in society. This study aimed to assess Hepatitis B vaccination status of high transmitter risk group and their knowledge attitude and practice regarding Body substance Isolation. Method: This questioner based cross sectional study was conducted in January 2013 to March 2014. 400 HCW comprising of 55% male and 45% female belonging to four groups 100 each doctor, nurse, Operation Theatre and clinical laboratory technician working at different tertiary hospitals in Karachi-Pakistan were included in the study. Results: 28% doctors, 20% nurses, 64% operation theatre and 68%lab-technician were fully immunized. Among rest 31% were unaware of vaccine, 45% did not consider themselves among high risk group, 15% expected management to get them vaccinated, 9% found it expensive. Biosafety practices were correctly performed by 42%. 29% performed injection safe practice, 10% aseptic rules and 19% properly sterilized equipment. Blood spill was immediately cleaned by 80% among them 48% applied disinfectant, 40% cleaned it water and detergent, 12% cleaned and disinfected. Blood samples disposal was 52% in any available container, 17% in dustbin and 30% in biohazard bags. In case of accidental needle stick exposure 62 encouraged bleeding, 19% applied alcohol, 11% washed with water, 8% waited for medical help. Regarding discarding used syringe 42% used engineered device, 44% common container, 10% bent needles and 4% one handed scoop technique. Warning symbols were identified by 32% amongst them 30% identified biohazard, 8% harmful, 12% inflammable and 50% danger signs. Conclusion: To prevent HCW from Hepatitis their complete immunization should be mandatory and rigid BSI protocol monitored daily.